Nuclear ribosomal internal transcribed spacer 1 (ITS1) variation in the Anastrepha fraterculus cryptic species complex (Diptera, Tephritidae) of the Andean region - Sutton, Bruce D. (2015)
The nuclear ribosomal internal transcribed spacer 1 (ITS1) was sequenced for Anastrepha fraterculus (Wiedemann, 1830) originating from 85 collections from the northern and central Andean countries of South America including Argentina (Tucumán), Bolivia, Perú, Ecuador, Colombia, and Venezuela. The ITS1 regions of additional specimens (17 collections) from Central America (México, Guatemala, Costa Rica, and Panamá), Brazil, Caribbean Colombia, and coastal Venezuela were sequenced and together with published sequences (Paraguay) provided context for interpretation. A total of six ITS1 sequence variants were recognized in the Andean region comprising four groups. Type I predominates in the southernmost range of A. fraterculus. Type II predominates in its northernmost range. In the central and northern Andes, the geographic distributions overlap and interdigitate with a strong elevational effect. A discussion of relationships between observed ITS1 types and morphometric types is included.